Evaluation of applying negative pressure in two different methods on the retention in upper complete dentures (In vivo). - ميهوب نور; محمود محمود (Latakia University Journal -Medical Sciences Series, 2022)
This study aims to evaluate the effect of applying resilient liners on the internal surface of the upper complete dentures in two different methods by forming negative pressure which may increase the retention in upper complete dentures and comparing the upper dentures retention values before and after methods application. Objective: Twenty follow-up edentulous patients have been selected from the removable prosthodontics department, Faculty of Dentistry, Tishreen University patients, to have their new complete dentures. In the first method, an auto polymerized soft resilient liner was applied to the upper complete dentures’ internal surface in form of mini suction cups with specific diameter and depth, and these mini suction cups look-alike octopus tentacles that can apply negative pressure on the denture bearing mucosa. The second method works on applying the soft resilient liner in parallel to dentures borders in a specific width and thickness, afterward, retention was measured in kilogram unit using a digital retention measurement device, medians were calculated from obtained results to be compared with values before and after two methods application. Results: There were statically significant differences between mean values of retention before and after the application of two methods, with a P =0,004 for mini suction cups methods and P=0.043 for applying border pressure. Conclusion:From the obtained results we can conclude that the soft resilient liner applications in the two methods may contribute to increase retention values in upper complete dentures. Keywords: complete denture retention, resilient liner, suction cups, border seal.